Efektivitas Penggunaan Metode Drill dalam Meningkatkan Kemampuan Menghafal pada Mata Pelajaran Al-Qur’an-Hadits: Studi Kualitatif Naturalistik di MAN 1 Kota Bekasi - Isnawati .; Munir Abas (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2015)
The purpose of this study was to exactly, hui how the effectiveness of using the drill method in enhancing the ability of learners to memorize the Qur'an subjects hadith MAN 1 Bekasi. From this study we can conclude some of the following: (1) The drill methods applied by teachers of the Quran Hadith in MAN 1 Bekasi City has been run in accordance with the objectives that have been formulated in the syllabus and lesson plans. Designed by teachers of the Quran Hadith before stints teaching; (2) The use of the drill method is quite effective with evidence that carried out once a week but 2 hours, 1 hour 45 minutes means 2 hours 90 minutes, at most two times a week. And the result is no change in the overall study better using drill further improved and the children memorize it more easily.